Chemical synthesis of human trefoil factor 1 (TFF1) and its homodimer provides novel insights into their mechanisms of action - Braga Emidio, Nayara; Baik, Hayeon; Lee, David; Stürmer, René; Heuer, Jörn; Elliott, Alysha G.; Blaskovich, Mark A.T.; Haupenthal, Katharina; Tegtmeyer, Nicole; Hoffmann, Werner; Schroeder, Christina I.; Muttenthaler, Markus (Chemical Communications, 2020)
TFF1 is a key peptide for gastrointestinal protection and repair. Its molecular mechanism of action remains poorly understood with synthetic intractability a recognised bottleneck. Here we describe the synthesis of TFF1 and its homodimer and their interactions with mucins andHelicobacter pylori. Synthetic access to TFF1 is an important milestone for probe and therapeutic development.
CRIS-Team Scopus Importer:2020-06-19